ANALISIS PEMBANGUNAN DESA SUNGAI PUTIH KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR (Studi Kasus Alokasi Dana Desa) - Perangin-Angin, Putri Sry Muliana Br; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Rural development is an essential element in the national development system that developed integrally. Implementation of rural development substance and essence or essentially involves 78% of the population and also the future of Indonesia itself. With the allocation of village funds, is expected to create equitable development, especially in rural areas will further improve the walfare and standard of living of rural people and encourage â€œthe active involmentâ€ of village government and the people of the village itself in the development process.This research was conduted in the village of Sungai Putih from East Kampar, Kampar distcrict. The purpose of this study was to analyze the implementation of rural development based on the use of Sungai Putih Allocation Of Village Funds. In this study, the researcher was using descriptive qualitative method. To obtain the data for this research, the researcher used techniques such as in depth interviews, direct observation and documentation.The result of this research, indicated that the implementation of rural development by the village fund allocation ha reached 70% or 80% of the expected. But rural development in this village is focused on the construction of buildings such as village offices and BPD reconstruction, as well as the manufactured of drainage channels so as not doing roadwork environment that has been severely damaged. The researched found there is less harmonious relationship between the government on village and BPD makes no involvement in the oversight of the development and allocation of village funds. The lacking of transparency of the village government to the village are involved and who served the government only three people because of the condition the village government leadership status officials donâ€™t have the authority to appoint a new village officers. So that it resulting in double position in the implementation of development tasks and management of village fund allocation.Key Words: Implementation, rural development, and Village Fund Allocation.